Complementary variable‐ and person‐centred approaches to the dimensionality of workaholism. Issue 1 (3rd June 2021) - Gillet, Nicolas; Morin, Alexandre J. S.; Ndiaye, Adama; Colombat, Philippe; Sandrin, Emilie; Fouquereau, Evelyne
Abstract: This research relies on complementary variable‐ and person‐centred approaches to investigate the underlying dimensionality of the workaholism construct. In three studies (Study 1: N  = 343 workers; Study 2: N  = 654 firefighters in Sample 1 and N  = 247 administrative and technical employees in Sample 2; and Study 3: N  = 153 nurses in Sample 1 and N  = 359 educators in Sample 2), the results showed that employees' workaholism ratings simultaneously reflected a global overarching workaholism construct, which co‐existed with two specific dimensions (working excessively and compulsively). In Study 1, global levels of self‐determined motivation were associated with higher global levels of workaholism, whereas perceived supervisor support was negatively related to global levels of workaholism. We then examined the distinct configurations, or profiles, taken by workaholism dimensions (global workaholism, and specific working excessively and compulsively; Studies 2 and 3) and psychological detachment (Study 3). Studies 2 and 3 also documented the associations between these workaholism profiles, and correlated predictor (e.g. supervisor support, workload) and outcome (e.g. emotional exhaustion, work performance) variables. Three of the four profiles identified were similar across studies ( Low Global and Average Specific Workaholism, Average Global and Specific Workaholism and High Global and Average Specific Workaholism ), whereas one profile was different across studies and samples. In both studies, the High Global and Average Specific Workaholism profile was associated with the worst correlated outcome variables (e.g. high levels of emotional exhaustion, low levels of job satisfaction).